2012
DOI: 10.1111/j.1463-6395.2012.00563.x
|View full text |Cite
|
Sign up to set email alerts
|

Histological structure of the female gonads and ovipositor of the European bitterling, Rhodeus amarus (Bloch, 1782) (Cyprinidae: Acheilognathinae)

Abstract: Khlopova, A.V. and Kul'bachnyi, S. 2013. Histological structure of the female gonads and ovipositor of the European bitterling, Rhodeus amarus (Bloch, 1782) (Cyprinidae: Acheilognathinae). -Acta Zoologica (Stockholm) 94: 355-363.We investigated the histological structure of the female gonads and ovipositor of the European bitterling, Rhodeus amarus. The base of the ovipositor was formed by the conical organ or 'eminence'. Based on the structure of the conical organ, including a special distribution of collagen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Khlopova and Kul'bachnyi () describe very well the histological structure of female gonads and ovipositor of fish. Based on our previous study (unpublished), we hypothesized that we found alterations in the fish reproductive system, which probably may be associated with untreated municipal wastewaters, which could possibly be contaminated with EDCs.…”
Section: Discussionmentioning
confidence: 99%
“…Khlopova and Kul'bachnyi () describe very well the histological structure of female gonads and ovipositor of fish. Based on our previous study (unpublished), we hypothesized that we found alterations in the fish reproductive system, which probably may be associated with untreated municipal wastewaters, which could possibly be contaminated with EDCs.…”
Section: Discussionmentioning
confidence: 99%